Medication Adherence and Health related Quality of life among Patients with Chronic Obstructive Pulmonary Disease in Pokhara - Acharya, Chandra Prasad; Yadav, Alok; Paudel, Kalpana; Thapaliya, Rekha; Duwadi, Vijaya (Journal of National Heart and Lung Society Nepal, 2024)
Background: Chronic obstructive pulmonary disease (COPD) is a common preventable and treatable chronic disease. Patients have to consume medicine for longer duration which usually leads to non adherent to medicine in long term due to various socio-economic factors such as financial status, economical status of patients. This study focuses on nature of medicine adherence among COPD patients, factors affecting medicine adherence of the patients and influence of medicine adherence on Health related Quality Of Life.Methods: A descriptive analysis study was done among known case of COPD cases after obtaining approval from ethical review board of NHRC. A written consent was obtained from all the participants. Morrisky Medication adherence scale was used to access medication adherence among patient where as st. George ’s Respiratory Questionnaire for COPD was used to evaluate Health related Quality of life of the patients. Results: Among 350 cases analyzed, majority (n= 217; 63%) of the cases were poorly adherence to medicine. There was significant association between rural residence of patients, poor financial status, low education status, longer disease duration, lack of financial support, nuclear family type and poor adherent to medicine (p< 0.05). There was also significant association between poor medicine adherent and poor Health related Quality of Life. (P < 0.05).Conclusion: These patients experienced a severe impact on their symptoms, considerable limitations in daily activities, a higher burden of disease, and an overall reduction in their quality of life.